The Correlation Analysis Between Supervisory Action And Organization Culture To Individual Performance Of Junior Accountant In Public Accounting Firm With Job Satisfaction As Intervening Variable - Murtanto, Murtanto; Djasmin, Melva (The International Journal of Accounting and Business Society, 2005)
The objective of this research is to analyze the impact of supervisory action, organizational structure, job satisfaction and individual performance junior accountants in public accounting firm. This study reports the results of a survey of 276 junior accountants from 17 small public accounting firms and 6 big public accounting firms.  Purposive method is used to define the sample. This study find that the two major elements of supervisory action recommended by the AECC, leadership and mentoring, and assignments, do not give impact on the job satisfaction.  Work condition give impact on the job satisfaction but job satisfaction do not give impact on the individual performance.  This study also find that the three elements of organizational culture, bureaucratic and innovative culture were negatively correlated but do not give impact on the job satisfaction, unexpectedly, supportive culture was positively correlated but do not give impact on the job satisfaction.  However, there are no significant differences between small public accounting firms and big public accounting firms for the supervisory actions and job satisfaction.  But there are significant differences between small and big public accounting firms for the individual performance. Keywords: supervisory action, organization culture, individual performance, job satisfaction